Extreme returns and corresponding events for JSE indices - Wright, Sarah Nicole (My University, 2012)
This research investigated the identification of short-term extreme returns on the Johannesburg Stock Exchange (JSE) and their corresponding events. The identification of the short-term extreme returns was accomplished through the method of uniform reduction, allowing the dates of the extreme returns to be detected through a probabilistic analysis. A qualitative content analysis was performed, utilising two major South African newspapers, to establish what events could have caused the extreme returns. The analysis was performed for four major indices over a 10-11 year period. The research showed that the JSE was affected by both local and international events. Major events such as the September 11 Terrorist Attacks, the Global Financial Crisis and the South African Power Crisis were identified as well as local events relating to interest rates, the release of economic data, monetary policy, and specific domestic political events. The context or environment in which an event occurs was found to be significant in determining the market reaction. The methodology utilised proved to be both effective and robust, but due to its exploratory and pioneering nature, still needs some refinement.
MBA thesis - WBS
Keywords: Extreme returns on Stock Markets; Investment; Johannesburg Securities Exchange